Diversity in chemical structures and biological properties of plant alkaloids - Bhambhani, Sweta; Kondhare, Kirtikumar R.; Giri, Ashok P. (Molecules, 2021)
Phytochemicals belonging to the group of alkaloids are signature specialized metabolites endowed with countless biological activities. Plants are armored with these naturally produced nitrogenous compounds to combat numerous challenging environmental stress conditions. Traditional and modern healthcare systems have harnessed the potential of these organic compounds for the treatment of many ailments. Various chemical entities (functional groups) attached to the central moiety are responsible for their diverse range of biological properties. The development of the characterization of these plant metabolites and the enzymes involved in their biosynthesis is of an utmost priority to deliver enhanced advantages in terms of biological properties and productivity. Further, the incorporation of whole/partial metabolic pathways in the heterologous system and/or the overexpression of biosynthetic steps in homologous systems have both become alternative and lucrative methods over chemical synthesis in recent times. Moreover, in-depth research on alkaloid biosynthetic pathways has revealed numerous chemical modifications that occur during alkaloidal conversions. These chemical reactions involve glycosylation, acylation, reduction, oxidation, and methylation steps, and they are usually responsible for conferring the biological activities possessed by alkaloids. In this review, we aim to discuss the alkaloidal group of plant specialized metabolites and their brief classification covering major categories. We also emphasize the diversity in the basic structures of plant alkaloids arising through enzymatically catalyzed structural modifications in certain plant species, as well as their emerging diverse biological activities. The role of alkaloids in plant defense and their mechanisms of action are also briefly discussed. Moreover, the commercial utilization of plant alkaloids in the marketplace displaying various applications has been enumerated.
Keywords: alkaloid; Biological activity; classification; defense; Enzyme; modification

Advanced genome editing strategies for manipulation of plant specialized metabolites pertaining to biofortification - Bhambhani, Sweta; Kondhare, Kirtikumar R.; Giri, Ashok P. (Phytochemistry Reviews, 2022)
Emerging trends in molecular biology have progressed the knowledge of plant specialized metabolites with respect to diversity in structure, function and biosynthetic pathways. Being powerful genome-editing tools, Zinc Finger Nuclease, Transcription Activator-Like Effector Nuclease, and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) systems have found potential application in genome and epigenome engineering. CRISPR/Cas9 is being used for studying the functions of multiple genes and gene families in plants. Our analysis suggests that although a rapid progress has occurred for utilization of CRISPR/Cas9 tool in crop improvement, limited studies are available for its application in manipulation of gene clusters of useful specialized metabolites in plants. In this review, after describing briefly about the recent advancements in genome editing techniques, we have further discussed their applicability in the modulation of metabolite production and biofortification of food crops. We have also emphasized the importance of CRISPR/Cas9-based targeted deletion of larger chromosomal fragments or gene clusters towards value addition of crop plants. The current policies for CRISPR/Cas9-edited crop plants in different countries and their acceptability in market place is also discussed. We propose that advanced genome editing techniques, including a multiplex CRISPR/Cas9 system could serve as a versatile tool for rewiring of metabolite gene clusters and improving the levels of useful metabolites in plants.
Keywords: Cas9; Chromosomal fragment; CRISPR; Gene cluster; Genome editing; Plant specialized metabolites